Turn Down the Heat: Why a 4°C Warmer World Must Be Avoided - World Bank (Washington, DC, 2012)
A new report synthesizing the latest scientific knowledge on global warming warns we’re on a path to a 4 degree Celsius warmer world by the end of the century—with huge implications for humanity.